The Effect of Audio and Video Modality on Perception of Reduced Forms: The Role of Web-Based Instruction - Reduced Forms in an L2 Listening Context - Gulozer, Kaine; Kocoglu, Zeynep (Igi Global, 2021)
Reduced forms (RFs) spoken by native English speakers have been challenging on the part of the second language (L2) learners. This chapter aims to address suprasegmental features to Turkish preparatory language school students in relation to L2 listening comprehension. Considering the limited research on RFs in learning English as a L2 context, this pre-test post-test control group design study aimed to explore whether the instruction of five RFs in sentential level results in any difference in listening comprehension test performance. The five forms entail contraction, assimilation, flap, elision, and linking. A total of 343 were recruited, and RFs instruction was delivered through the web page designated for the study for five weeks, and the performance of the eight groups was measured twice throughout the study. The findings indicated that sentence level of RFs instruction through web-based learning facilitates the listening comprehension of RFs.
Keywords: English; Assimilation; Impact